2021
DOI: 10.4103/jfmpc.jfmpc_2436_20
|View full text |Cite
|
Sign up to set email alerts
|

Profile of multimorbidity in outpatients attending public healthcare settings

Abstract: Background: Multimorbidity, the co-occurrence of two or more long-term conditions (LTC) in individuals, is associated with greater healthcare utilization, expenditure, and premature mortality, thus positing a challenge for patients and healthcare providers. Given its sparsely available epidemiological evidence, we aimed to describe the profile of multimorbidity in a representative sample of public healthcare outpatients in India. Methods: A facility-based cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Our study found females had a higher likelihood of having multimorbidity, which is consistent with the findings of previous studies done among patients visiting primary care in India [ 28 , 32 ]. In LMICs such as India, women are often vulnerable as they are often economically dependent on other family members.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found females had a higher likelihood of having multimorbidity, which is consistent with the findings of previous studies done among patients visiting primary care in India [ 28 , 32 ]. In LMICs such as India, women are often vulnerable as they are often economically dependent on other family members.…”
Section: Discussionsupporting
confidence: 93%
“…We found multimorbidity to be associated with urban residents, affluent groups, and Southern India, which is similar with the findings of previous studies conducted among individual-level participants in India [ 32 , 33 ]. Although these findings suggest these groups to have more multimorbidity, it could be due to various other social factors.…”
Section: Discussionsupporting
confidence: 91%
“…In LMICs such as India, multimorbidity is on the rise; evident by a recent study that estimated a 55% prevalence among adults attending public healthcare facilities. 5 However, the evidence on multimorbidity burden is scattered across various studies done in either small samples or particular regions, but no study to date has synthesized the national estimates. Although, the high prevalence indicates an additional burden on the already swamped healthcare system, the national estimate of multimorbidity burden could help in evidence based guidance to plan changes to the structure and delivery of primary care.…”
Section: Introductionmentioning
confidence: 99%